PEEK composite insulated wire and preparation method thereof

By adding carbon fiber and glass fiber to the resin layer of PEEK insulating wire and using polyimide and nanotubes as modifiers to form a complex interlaced network structure, the problem of insufficient insulation performance and reliability of PEEK insulating wire in high voltage and high temperature environments is solved, and significant improvements in mechanical strength and high temperature resistance are achieved.

CN119811755AActive Publication Date: 2025-04-11TONGLING JINGDA SPECIAL MAGNET WIRE CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510301112.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-11
Estimated Expiration
2045-03-14

AI Technical Summary

Technical Problem

The insulation performance and reliability of a single PEEK insulating layer in high voltage and high temperature environments still need to be improved, and its high temperature resistance and mechanical strength are not sufficient to meet the needs of modern electrical equipment.

Method used

Using PEEK composite insulating wire, a complex interlaced network structure is formed by adding carbon fiber and glass fiber to the resin layer as filler, and using polyimide and nanotubes as modifiers to form a complex interlaced network structure to improve the mechanical strength and high temperature resistance of PEEK.

Benefits of technology

It significantly improves the mechanical strength and high temperature resistance of PEEK composite insulated wire, and enhances its insulation performance and reliability in high voltage and high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of electromagnetic wires, and particularly discloses a PEEK composite insulated wire and a preparation method thereof. The PEEK composite insulated wire comprises a battery cell and a resin layer wrapping the battery cell, and the resin layer comprises the following raw materials in parts by weight: 100 parts of polyether-ether-ketone; 10 to 20 parts of filler; the filler comprises carbon fibers and glass fibers, the filler is a modified filler modified by a modifier, and the modifier comprises polyimide and nanotubes. The preparation method comprises the following steps: S1, preparing raw materials of the resin layer: drying PEEK powder at 120 DEG C for 24 hours, and mixing and melting the filler and the PEEK powder to obtain the raw materials of the resin layer; and S2, preparing the composite insulated wire. The composite insulated wire can be used in electrical equipment such as automobiles, and has the advantages of high temperature resistance, high strength and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electromagnetic wires, and more specifically, to a PEEK composite insulated wire and a preparation method thereof. Background Art

[0002] Polyetheretherketone (PEEK) is an excellent thermoplastic engineering plastic with high heat resistance, excellent mechanical properties and easy processing characteristics. It has broad application prospects in the field of electromagnetic wire insulation. However, the insulation performance and reliability of a single PEEK insulation layer under harsh environments such as high voltage and high temperature still need to be improved.

[0003] When the insulated wire is used, the current flows through the insulated wire and the temperature increases due to the heat generated. The electrical equipment used in automobiles and other equipment is becoming smaller and higher in output year by year, which will cause the temperature inside the device to rise. Under high temperature, the coating resin layer of the insulated wire used in the equipment will be thermally degraded and shrink. Therefore, the high temperature resistance and mechanical strength of PEEK insulated wire need to be further improved. Summary of the invention

[0004] In order to improve the defects of poor high temperature resistance and mechanical strength of PEEK insulated wire, the present application provides a PEEK composite insulated wire and a preparation method thereof, adopting the following technical solutions: In a first aspect, the present application provides a PEEK composite insulated wire, comprising a battery core and a resin layer wrapped outside the battery core, wherein the resin layer comprises the following raw materials in parts by weight: 100 parts of polyetheretherketone; 10-20 parts of filler; The filler comprises carbon fiber and glass fiber, and the filler is a modified filler modified by a modifier, and the modifier comprises polyimide and nanotube.

[0005] By adopting the above technical scheme, carbon fiber and glass fiber are preferably used as fillers. Carbon fiber and glass fiber can introduce an interlaced network structure into PEEK, effectively improving the strength of PEEK. In addition, both carbon fiber and glass fiber have better high temperature resistance, and can introduce a heat-resistant network skeleton structure into PEEK, thereby improving the high temperature resistance of PEEK.

[0006] Preferably, polyimide and nanotubes are used as modifiers to modify the filler. Polyimide has high rigidity, excellent mechanical properties and high temperature resistance, and can improve the surface energy of the filler, improve the compatibility between the filler and PEEK, and improve the dispersion uniformity of the filler in PEEK to form a uniform and dense network structure. Under the cooperation of polyimide and nanotubes, the nanotubes can adhere to the surface of the filler under the action of polyimide, and construct a composite structure of a long linear structure-short linear structure with the filler, which can form a more complex staggered network structure. The nanotubes can serve as anchors to improve the bonding effect between the filler and PEEK, that is, further improve the mechanical strength of PEEK.

[0007] Optionally, the polyimide is a polyimide containing an etherketone structure.

[0008] By adopting the above technical solution, preferably using polyimide with an ether ketone structure as a modifier, the similar compatibility characteristics of the ether ketone structure are utilized to improve the compatibility and dispersion effect of the filler in PEEK.

[0009] Optionally, the nanotubes include any one of titanium dioxide nanotubes, silicon dioxide nanotubes, and carbon nitride nanotubes.

[0010] By adopting the above technical solution, preferably using titanium dioxide nanotubes, silicon dioxide nanotubes or carbon nitride nanotubes, they can all be loaded on the filler surface through polyimide, serve as anchor points for the filler, build a complex cross-linked network structure in PEEK, and stably improve the mechanical strength of PEEK.

[0011] Optionally, the silica nanotubes are amino-treated silica nanotubes.

[0012] By adopting the above technical scheme, the silica nanotubes are subjected to an amination treatment, and amino groups are grafted on the surface of the silica nanotubes. The strong hydrogen bond interaction between the amino groups and the polyimide molecules is utilized to improve the connection strength between the silica nanotubes and the filler, so that the silica nanotubes are stably used as anchor points, and at the same time, the packing density between the polyimide molecular chains can be effectively enhanced, thereby improving the wear resistance of PEEK and further improving the mechanical strength of the resin layer.

[0013] Optionally, the preparation of the modifier is as follows: Preparation of polyamic acid: APBP and PMDA were dried for 12 h, and then APBP was dissolved in a suitable amount of DMAc solution under nitrogen, and stirred evenly. PMDA was added, and the polyamic acid (PAA) solution was stirred for 24 h, and then diluted with DMAc to a 0.25% precursor solution. Preparation of the modifier: The nanotubes are crushed and dispersed in a DMAc solution to obtain a dispersion, and the dispersion is mixed with a precursor solution to obtain a modifier.

[0014] Optionally, the polyetheretherketone is a modified polyetheretherketone grafted with a rigid group, and the rigid group includes any one or more of a carbonyl group, a polyphenyl ether group or a biphenyl group.

[0015] By adopting the above technical scheme, rigid groups are grafted on the polyetheretherketone molecular chain. The carbonyl group, polyphenyl ether group and biphenyl group have different rigidity strengths. Grafting on the polyetheretherketone molecular chain can adjust the flexibility between the polyetheretherketone molecular chains, so that the polyetheretherketone obtains excellent shape memory properties. The resin layer is composed of a fiber skeleton and polyetheretherketone with shape memory properties. The resin layer is not easily damaged and can protect the battery cell for a long time.

[0016] Optionally, the modified polyetheretherketone is prepared as follows: under the protection of an argon atmosphere, diphenyl sulfone is heated in a diphenyl sulfone container to melt the diphenyl sulfone, and then 4,4'-difluorobenzophenone, hydroquinone, biphenol, 4,4'-dihydroxydiphenyl ether, and a mixed salt of sodium carbonate and potassium carbonate are added into the system, and uniform stirring is maintained. The system is kept at 220°C for 2h, 250°C and 290°C for 1h each, and finally polymerized at 310°C for 2h. The product is discharged into water, the product is crushed, washed with ethanol and water 10 times each, and then dried in an oven to obtain the modified polyetheretherketone.

[0017] By adopting the above technical scheme, the preparation of modified polyetheretherketone is optimized. By combining the more rigid biphenyl groups with the polyphenyl ether segments, the molecular structure is made more like the structure of a shape memory polymer, which further improves the shape memory properties of the polymer and enables the resin layer to protect the battery cell for a long time.

[0018] Optionally, the mass ratio of the 4,4'-dihydroxydiphenyl ether to biphenol is 1-3:7-9.

[0019] By adopting the above technical solution, the addition amount of polyphenyl ether groups is optimized. At a suitable addition amount, the modified polyetheretherketone can obtain a better shape memory effect, and can cooperate with the filler network to protect the battery cell for a long time.

[0020] Optionally, the glass fiber is bioactive glass fiber.

[0021] By adopting the above technical solution, the bioactive glass fiber is composed of chemical components such as CaO, P2O5, SiO2, Na2O, etc., and the bioactive glass fiber has better compatibility with polyetheretherketone, thereby improving the reinforcing effect of the filler on polyetheretherketone.

[0022] Optionally, the surface of the glass fiber is wrapped with a polyethersulfone-sodium polystyrene sulfonate composite layer.

[0023] By adopting the above technical scheme, polyethersulfone can be cracked to produce macromolecular free radicals, which undergo free radical polymerization reaction with sodium 4-styrenesulfonate to form a polyethersulfone-sodium polystyrenesulfonate composite material. The polyethersulfone-sodium polystyrenesulfonate composite material has better high temperature resistance, can cover the surface of glass fiber in the form of a thin layer and microspheres, introduce active groups into the glass fiber, and further promote the bonding strength between glass fiber and polyetheretherketone.

[0024] In a second aspect, the present application provides a method for preparing a PEEK composite insulated wire, which adopts the following technical solution: A method for preparing a PEEK composite insulated wire comprises the following steps: S1. Preparation of resin layer raw materials: drying PEEK powder at 120° C. for 24 h, mixing filler with PEEK powder, and melting to obtain resin layer raw materials; S2. Preparation of composite insulated wire: Extruding the resin layer raw material outside the battery core to obtain a composite insulated wire.

[0025] In summary, this application has the following beneficial effects: 1. Since the present application adopts polyimide and nanotubes as modifiers to modify the filler, polyimide has high rigidity, excellent mechanical properties and high temperature resistance, and can improve the surface energy of the filler, improve the compatibility between the filler and PEEK, and improve the dispersion uniformity of the filler in PEEK to form a uniform and dense network structure. With the cooperation of polyimide and nanotubes, the nanotubes can adhere to the surface of the filler under the action of polyimide, and construct a composite structure of long linear structure-short linear structure with the filler, which can form a more complex staggered network structure. The nanotubes can serve as anchor points to improve the bonding effect between the filler and PEEK, that is, further improve the mechanical strength of PEEK.

[0026] 2. In the present application, it is preferred to perform an amination treatment on the silica nanotubes, graft amino groups on the surface of the silica nanotubes, and utilize the strong hydrogen bond interaction between the amino groups and the polyimide molecules to improve the connection strength between the silica nanotubes and the filler, so that the silica nanotubes can be stably used as anchor points, and at the same time, the packing density between the polyimide molecular chains can be effectively enhanced, thereby improving the wear resistance of PEEK and further improving the mechanical strength of the resin layer.

[0027] 3. The present application adopts the method of grafting rigid groups on the polyetheretherketone molecular chain. The carbonyl group, polyphenyl ether group and biphenyl group have different rigidity strengths. Grafting on the polyetheretherketone molecular chain can adjust the flexibility between the polyetheretherketone molecular chains, so that the polyetheretherketone obtains excellent shape memory properties. The resin layer is composed of a fiber skeleton and polyetheretherketone with shape memory properties. The resin layer is not easily damaged and can protect the battery cell for a long time. DETAILED DESCRIPTION

[0028] The present application is further described in detail below with reference to the embodiments.

[0029] Preparation Example Modifier Preparation Example Preparation Example 1 The preparation of the modifier is as follows: Preparation of polyamic acid: Take 0.05 mol APBP (pyromellitic dianhydride) and 0.05 mol PMDA (4,4′-bis(3-aminophenoxy)benzophenone) respectively, dry them at 80°C for 12 hours, dissolve APBP in a solution containing an appropriate amount of DMAc (N,N-dimethylacetamide) under nitrogen, stir evenly, add PMDA, stir the polyamic acid (PAA) solution for 24 hours, and dilute it with DMAc to a 0.25% precursor solution; Preparation of the modifier: Silica nanotubes were crushed and dispersed in a DMAc solution to obtain a 1 mg / mL dispersion, and the dispersion was mixed with a precursor solution to obtain a modifier with a nanotube content of 0.1%.

[0030] Preparation Example 2 The preparation of the modifier is as follows: Preparation of polyamic acid: 0.05 mol APBP and 0.05 mol PMDA were taken and dried at 80 °C for 12 h, then APBP was dissolved in a suitable amount of DMAc solution under nitrogen, stirred evenly, PMDA was added, and the polyamic acid (PAA) solution was stirred for 24 h, and then diluted with DMAc to a 0.25% precursor solution; Preparation of the modifier: CNTs were crushed and dispersed in a DMAc solution to obtain a 1 mg / mL dispersion, and the dispersion was mixed with a precursor solution to obtain a modifier with a nanotube content of 0.1%.

[0031] Preparation Example 3 The preparation of the modifier is as follows: Preparation of polyamic acid: 0.05 mol APBP and 0.05 mol PMDA were taken and dried at 80 °C for 12 h, then APBP was dissolved in a suitable amount of DMAc solution under nitrogen, stirred evenly, PMDA was added, and the polyamic acid (PAA) solution was stirred for 24 h, and then diluted with DMAc to a 0.25% precursor solution; Preparation of the modifier: Aminated silica nanotubes were crushed and dispersed in a DMAc solution to obtain a 1 mg / mL dispersion, and the dispersion was mixed with a precursor solution to obtain a modifier with a nanotube content of 0.1%.

[0032] Preparation example of modified polyetheretherketone Preparation Example 4 The preparation of modified polyetheretherketone is as follows: argon is introduced into a three-necked flask equipped with an argon inlet and a mechanical stirring device. After the argon fills the flask, diphenyl sulfone (133.5 g) is added into the flask and heated to 130°C. After the diphenyl sulfone is completely melted, 4,4'-difluorobenzophenone (33.39 g, 0.153 mol), hydroquinone (11.56 g, 0.105 mol), 4,4'-dihydroxybenzophenone (9.94 g, 0.045 mol), sodium carbonate (19.08 g, 0.18 mol) and potassium carbonate (0.21 g, 0.0015 mol) are added into the system. Then, stir evenly under an argon atmosphere, slowly heat up, and start to carry water after rising to 220°C. After staying for 2 hours, the system is completely watered, and then continue to heat up, staying at 250°C and 290°C for 1 hour respectively, and then heat up to 310°C for polymerization. After the system in the bottle is highly viscous, pour the product into deionized water (3L) to obtain a white fibrous crude product. Then, the crude product is placed in a high-speed mixer for crushing, and washed ten times with ethanol and deionized water respectively. Then, the product is placed in a vacuum oven and dried at 120°C for 12 hours to finally obtain a white product, which is the modified polyetheretherketone.

[0033] Preparation Example 5 The preparation of modified polyetheretherketone is as follows: argon is introduced into a three-necked flask equipped with an argon inlet and a mechanical stirring device. After the argon fills the flask, diphenyl sulfone (133.5 g) is added into the flask and heated to 130°C. After the diphenyl sulfone is completely melted, 4,4'-difluorobenzophenone (33.39 g, 0.153 mol), hydroquinone (14.86 g, 0.135 mol), biphenylene glycol (2.79 g, 0.015 mol), sodium carbonate (19.08 g, 0.18 mol) and potassium carbonate (0.21 g, 0.0015 mol) are added into the system. Then, stir evenly under an argon atmosphere, slowly heat up, and start to carry water after rising to 220°C. After staying for 2 hours, the system is completely watered, and then continue to heat up, staying at 250°C and 290°C for 1 hour respectively, and then heat up to 310°C for polymerization. After the system in the bottle is highly viscous, pour the product into deionized water (3L) to obtain a white fibrous crude product. Then, the crude product is placed in a high-speed mixer for crushing, and washed ten times with ethanol and deionized water respectively. Then, the product is placed in a vacuum oven and dried at 120°C for 12 hours to finally obtain a white product, which is the modified polyetheretherketone.

[0034] Preparation Example 6 The modified polyetheretherketone is prepared as follows: argon is introduced into a three-necked flask equipped with an argon inlet and a mechanical stirring device. After the argon fills the flask, diphenyl sulfone (133.5 g) is added into the flask, and the flask is heated to 130° C. After the diphenyl sulfone is completely melted, 4,4'-difluorobenzophenone (33.39 g, 0.153 mol), 4,4'-dihydroxydiphenyl ether (9.10 g, 0.045 mol), biphenol (19.55 g, 0.105 mol), sodium carbonate (19.08 g, 0.18 mol) and potassium carbonate (0.21 g, 0.0015 mol) are added into the system. Then, stir evenly under an argon atmosphere, slowly heat up, and start to carry water after rising to 220°C. After staying for 2 hours, the system is completely watered, and then continue to heat up, staying at 250°C and 290°C for 1 hour respectively, and then heat up to 310°C for polymerization. After the system in the bottle is highly viscous, pour the product into deionized water (3L) to obtain a white fibrous crude product. Then, the crude product is placed in a high-speed mixer for crushing, and washed ten times with ethanol and deionized water respectively. Then, the product is placed in a vacuum oven and dried at 120°C for 12 hours to finally obtain a white product, modified polyetheretherketone.

[0035] Preparation Example 7 PES (polyethersulfone) and NaSS (sodium styrene sulfonate) were dried in a vacuum oven at 120°C for 24 hours. Then, NaSS (6wt%) and PES (2wt%) were completely dissolved in DMF, and the mixed solution was added to an internally illuminated glass reaction bottle, and then degassed with N2 for 30 minutes. A mercury lamp (254nm, 28W, radiation intensity of 0.6mw / cm 2 ) The mixed solution was irradiated at room temperature. During the irradiation period, the solution was magnetically stirred (500r / min) and filled with N2 gas. The irradiation time was 30min, and PES-NaPSS was obtained. 0.9g PES-NaPSS was added to a mixed solution of 2g DMSO and 15.1g dichloromethane, and magnetic stirring was performed until completely dissolved. 97.1g deionized water was added, and then placed in an ice bath environment. Then, an ultrasonic cell crusher (power of 1800W, frequency of 20kHz) was used for ultrasonication for 30min to form a PES-NaPSS emulsion. Finally, the dichloromethane in the emulsion was recovered by a rotary evaporator to obtain a coating. The coating was applied to the surface of the glass fiber and dried to obtain a modified glass fiber.

[0036] Example Examples 1-3 On the one hand, the present application provides a PEEK composite insulated wire, comprising a battery core and a resin layer wrapped outside the battery core, wherein the resin layer comprises the following raw materials: polyetheretherketone and filler; The filler comprises carbon fiber and glass fiber of equal mass. The filler is a modified filler modified by a modifier. The modifier is the modifier prepared in Preparation Example 1.

[0037] Preparation of modified filler: immerse the filler in the modifier for 2 hours, remove it, dry it at 80°C, heat it to 200°C and keep it for 1 hour, heat it to 300°C and keep it for 1 hour to obtain the modified filler.

[0038] On the other hand, the present application provides a method for preparing a PEEK composite insulated wire, comprising the following steps: S1. Preparation of resin layer raw materials: drying PEEK powder at 120° C. for 24 h, mixing filler with PEEK powder, and melting to obtain resin layer raw materials; S2. Preparation of composite insulated wire: Extruding the resin layer raw material outside the battery core to obtain a composite insulated wire.

[0039] Table 1 Composition of Examples 1-3

[0040] Example 4 On the one hand, the present application provides a PEEK composite insulated wire, comprising a battery core and a resin layer wrapped outside the battery core, wherein the resin layer comprises the following raw materials: 100 kg of polyetheretherketone and 20 kg of filler; The filler comprises carbon fiber and glass fiber of equal mass, and the filler is a modified filler modified by a modifier, and the modifier is the modifier prepared in Preparation 2.

[0041] Preparation of modified filler: immerse the filler in the modifier for 2 hours, remove it, dry it at 80°C, heat it to 200°C and keep it for 1 hour, heat it to 300°C and keep it for 1 hour to obtain the modified filler.

[0042] On the other hand, the present application provides a method for preparing a PEEK composite insulated wire, comprising the following steps: S1. Preparation of resin layer raw materials: drying PEEK powder at 120° C. for 24 h, mixing filler with PEEK powder, and melting to obtain resin layer raw materials; S2. Preparation of composite insulated wire: Extruding the resin layer raw material outside the battery core to obtain a composite insulated wire.

[0043] Example 5 On the one hand, the present application provides a PEEK composite insulated wire, comprising a battery core and a resin layer wrapped outside the battery core, wherein the resin layer comprises the following raw materials: polyetheretherketone and filler; The filler comprises carbon fiber and glass fiber of equal mass. The filler is a modified filler modified by a modifier. The modifier is the modifier prepared in Preparation Example 3.

[0044] Preparation of modified filler: immerse the filler in the modifier for 2 hours, remove it, dry it at 80°C, heat it to 200°C and keep it for 1 hour, heat it to 300°C and keep it for 1 hour to obtain the modified filler.

[0045] On the other hand, the present application provides a method for preparing a PEEK composite insulated wire, comprising the following steps: S1. Preparation of resin layer raw materials: drying PEEK powder at 120° C. for 24 h, mixing filler with PEEK powder, and melting to obtain resin layer raw materials; S2. Preparation of composite insulated wire: Extruding the resin layer raw material outside the battery core to obtain a composite insulated wire.

[0046] Example 6 On the one hand, the present application provides a PEEK composite insulated wire, comprising a battery core and a resin layer wrapped outside the battery core, wherein the resin layer comprises the following raw materials: polyetheretherketone and filler; The filler comprises carbon fiber and glass fiber of equal mass. The filler is a modified filler modified by a modifier. The modifier is the modifier prepared in Preparation Example 3. The polyetheretherketone is the modified polyetheretherketone prepared in Preparation Example 4.

[0047] Preparation of modified filler: immerse the filler in the modifier for 2 hours, remove it, dry it at 80°C, heat it to 200°C and keep it for 1 hour, heat it to 300°C and keep it for 1 hour to obtain the modified filler.

[0048] On the other hand, the present application provides a method for preparing a PEEK composite insulated wire, comprising the following steps: S1. Preparation of resin layer raw materials: drying PEEK powder at 120° C. for 24 h, mixing filler with PEEK powder, and melting to obtain resin layer raw materials; S2. Preparation of composite insulated wire: Extruding the resin layer raw material outside the battery core to obtain a composite insulated wire.

[0049] Example 7 On the one hand, the present application provides a PEEK composite insulated wire, comprising a battery core and a resin layer wrapped outside the battery core, wherein the resin layer comprises the following raw materials: polyetheretherketone and filler; The filler comprises carbon fiber and glass fiber of equal mass. The filler is a modified filler modified by a modifier. The modifier is the modifier prepared in Preparation Example 3. The polyetheretherketone is the modified polyetheretherketone prepared in Preparation Example 5.

[0050] Preparation of modified filler: immerse the filler in the modifier for 2 hours, remove it, dry it at 80°C, heat it to 200°C and keep it for 1 hour, heat it to 300°C and keep it for 1 hour to obtain the modified filler.

[0051] On the other hand, the present application provides a method for preparing a PEEK composite insulated wire, comprising the following steps: S1. Preparation of resin layer raw materials: drying PEEK powder at 120° C. for 24 h, mixing filler with PEEK powder, and melting to obtain resin layer raw materials; S2. Preparation of composite insulated wire: Extruding the resin layer raw material outside the battery core to obtain a composite insulated wire.

[0052] Example 8 On the one hand, the present application provides a PEEK composite insulated wire, comprising a battery core and a resin layer wrapped outside the battery core, wherein the resin layer comprises the following raw materials: polyetheretherketone and filler; The filler comprises carbon fiber and glass fiber of equal mass. The filler is a modified filler modified by a modifier. The modifier is the modifier prepared in Preparation Example 3. The polyetheretherketone is the modified polyetheretherketone prepared in Preparation Example 6.

[0053] Preparation of modified filler: immerse the filler in the modifier for 2 hours, remove it, dry it at 80°C, heat it to 200°C and keep it for 1 hour, heat it to 300°C and keep it for 1 hour to obtain the modified filler.

[0054] On the other hand, the present application provides a method for preparing a PEEK composite insulated wire, comprising the following steps: S1. Preparation of resin layer raw materials: drying PEEK powder at 120° C. for 24 h, mixing filler with PEEK powder, and melting to obtain resin layer raw materials; S2. Preparation of composite insulated wire: Extruding the resin layer raw material outside the battery core to obtain a composite insulated wire.

[0055] Example 9 On the one hand, the present application provides a PEEK composite insulated wire, comprising a battery core and a resin layer wrapped outside the battery core, wherein the resin layer comprises the following raw materials: polyetheretherketone and filler; The filler comprises carbon fiber and glass fiber of equal mass. The filler is a modified filler modified by a modifier. The modifier is the modifier prepared in Preparation Example 3. The polyetheretherketone is the modified polyetheretherketone prepared in Preparation Example 5. The glass fiber is bioactive glass fiber.

[0056] Preparation of modified filler: immerse the filler in the modifier for 2 hours, remove it, dry it at 80°C, heat it to 200°C and keep it for 1 hour, heat it to 300°C and keep it for 1 hour to obtain the modified filler.

[0057] On the other hand, the present application provides a method for preparing a PEEK composite insulated wire, comprising the following steps: S1. Preparation of resin layer raw materials: drying PEEK powder at 120° C. for 24 h, mixing filler with PEEK powder, and melting to obtain resin layer raw materials; S2. Preparation of composite insulated wire: Extruding the resin layer raw material outside the battery core to obtain a composite insulated wire.

[0058] Example 10 On the one hand, the present application provides a PEEK composite insulated wire, comprising a battery core and a resin layer wrapped outside the battery core, wherein the resin layer comprises the following raw materials: polyetheretherketone and filler; The filler includes carbon fiber and glass fiber of equal mass. The filler is a modified filler modified by a modifier. The modifier is the modifier prepared in Preparation Example 3, the polyetheretherketone is the modified polyetheretherketone prepared in Preparation Example 5, and the glass fiber is the glass fiber prepared in Preparation Example 7.

[0059] Preparation of modified filler: immerse the filler in the modifier for 2 hours, remove it, dry it at 80°C, heat it to 200°C and keep it for 1 hour, heat it to 300°C and keep it for 1 hour to obtain the modified filler.

[0060] On the other hand, the present application provides a method for preparing a PEEK composite insulated wire, comprising the following steps: S1. Preparation of resin layer raw materials: drying PEEK powder at 120° C. for 24 h, mixing filler with PEEK powder, and melting to obtain resin layer raw materials; S2. Preparation of composite insulated wire: Extruding the resin layer raw material outside the battery core to obtain a composite insulated wire.

[0061] Comparative Example Comparative Example 1 The difference between this comparative example and Example 3 is that the filler in this comparative example is not modified by a modifier.

[0062] Comparative Example 2 The difference between this comparative example and Example 3 is that the modifier in this comparative example only includes polyimide.

[0063] Performance testing (1) Mechanical property test: The tensile strength of the resin layer was tested using an EZ-LX HS universal material testing machine (Shimadzu, Japan) at a tensile rate of 0.5 mm / min.

[0064] (2) Thermal stability test: The thermal stability of the resin layer was tested under the conditions of air flow rate: 50 mL / min, temperature range: 100-800 °C, and heating rate: 10 °C / min.

[0065] Table 2 Performance test

[0066] Combining the performance test comparison in Table 2, we can find that: 1. By comparing Examples 1-3 with Comparative Examples 1-2, it can be found that the high temperature resistance and mechanical properties of the insulated wires prepared in Examples 1-3 are improved, which indicates that in the present application, polyimide and nanotubes are used as modifiers to modify the filler. Polyimide has high rigidity, excellent mechanical properties and high temperature resistance, and can improve the surface energy of the filler, improve the compatibility between the filler and PEEK, and improve the dispersion uniformity of the filler in PEEK to form a uniform and dense network structure. In the cooperation of polyimide and nanotubes, the nanotubes can adhere to the surface of the filler under the action of polyimide, and construct a composite structure of a long linear structure-short linear structure with the filler, which can form a more complex staggered network structure. The nanotubes can serve as anchors to improve the bonding effect between the filler and PEEK, that is, further improve the mechanical strength of PEEK.

[0067] 2. By comparing Examples 4-5 with Example 3, it can be found that the mechanical strength and high temperature resistance of the insulated wires prepared in Examples 4-5 are improved, which means that in the present application, the silica nanotubes are subjected to amination treatment, and amino groups are grafted on the surface of the silica nanotubes. The strong hydrogen bond interaction between the amino groups and the polyimide molecules is utilized to improve the connection strength between the silica nanotubes and the filler, so that the silica nanotubes are stabilized as anchor points, and at the same time, the packing density between the polyimide molecular chains can be effectively enhanced, thereby improving the wear resistance of PEEK and further improving the mechanical strength of the resin layer.

[0068] 3. By comparing Examples 6-8 with Example 3, it can be found that the mechanical strength and high temperature resistance of the insulated wires prepared in Examples 6-8 are improved, which means that in the present application, rigid groups are grafted on the polyetheretherketone molecular chain. The carbonyl group, polyphenyl ether group and biphenyl group have different rigid strengths, and the flexibility between the polyetheretherketone molecular chains can be adjusted by grafting on the polyetheretherketone molecular chain, so that the polyetheretherketone obtains excellent shape memory properties. The resin layer is composed of a fiber skeleton and polyetheretherketone with shape memory properties. The resin layer is not easily damaged and can protect the battery cell for a long time.

[0069] 4. By comparing Examples 9-10 with Example 3, it can be found that the mechanical strength and high temperature resistance of the insulated wires prepared in Examples 9-10 are improved, which indicates that polyethersulfone in the present application can be cleaved to produce macromolecular free radicals, and undergo free radical polymerization reaction with sodium 4-styrenesulfonate to form a polyethersulfone-sodium polystyrenesulfonate composite material. The polyethersulfone-sodium polystyrenesulfonate composite material has better high temperature resistance, can cover the surface of the glass fiber in the form of a thin layer and microspheres, introduce active groups into the glass fiber, and further promote the bonding strength between the glass fiber and polyetheretherketone.

[0070] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A PEEK composite insulated wire, characterized in that: It comprises a battery core and a resin layer wrapped outside the battery core, wherein the resin layer comprises the following raw materials in parts by weight: 100 parts of polyetheretherketone; 10-20 parts of filler; The filler comprises carbon fiber and glass fiber, and the filler is a modified filler modified by a modifier, and the modifier comprises polyimide and nanotube.

2. A PEEK composite insulated wire according to claim 1, characterized in that: The polyimide is a polyimide containing an ether ketone structure.

3. A PEEK composite insulated wire according to claim 2, characterized in that: The nanotubes include any one of titanium dioxide nanotubes, silicon dioxide nanotubes and carbon nitride nanotubes.

4. A PEEK composite insulated wire according to claim 3, characterized in that: The silicon dioxide nanotubes are amino-treated silicon dioxide nanotubes.

5. The PEEK composite insulated wire according to claim 2, characterized in that: The preparation of the modifier is as follows: Preparation of polyamic acid: APBP and PMDA were dried for 12 h, and then APBP was dissolved in a suitable amount of DMAc solution under nitrogen, and stirred evenly. PMDA was added, and the polyamic acid (PAA) solution was stirred for 24 h, and then diluted with DMAc to a 0.25% precursor solution. Preparation of the modifier: The nanotubes are crushed and dispersed in a DMAc solution to obtain a dispersion, and the dispersion is mixed with a precursor solution to obtain a modifier.

6. The PEEK composite insulated wire according to claim 1, characterized in that: The polyetheretherketone is a modified polyetheretherketone grafted with a rigid group, and the rigid group includes any one or more of a carbonyl group, a polyphenyl ether group or a biphenyl group.

7. A PEEK composite insulated wire according to claim 6, characterized in that: The modified polyetheretherketone is prepared as follows: under the protection of an argon atmosphere, diphenyl sulfone is placed in a container, and after heating to melt the diphenyl sulfone, 4,4'-difluorobenzophenone, hydroquinone, biphenylene glycol, 4,4'-dihydroxydiphenyl ether, and a mixed salt of sodium carbonate and potassium carbonate are added into the system, and uniform stirring is maintained, and the system is kept at 220°C for 2 hours, 250°C and 290°C for 1 hour respectively, and finally polymerized at 310°C for 2 hours, the product is discharged into water, the product is crushed, washed with ethanol and water for 10 times respectively, and then dried in an oven to finally obtain the modified polyetheretherketone.

8. The PEEK composite insulated wire according to claim 7, characterized in that: The mass ratio of the 4,4'-dihydroxydiphenyl ether to biphenyl diphenol is 1-3:7-9.

9. The PEEK composite insulated wire according to claim 1, characterized in that: The surface of the glass fiber is wrapped with a polyethersulfone-sodium polystyrene sulfonate composite layer.

10. The method for preparing a PEEK composite insulated wire according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Preparation of resin layer raw materials: drying PEEK powder at 120° C. for 24 h, mixing filler with PEEK powder, and melting to obtain resin layer raw materials; S2. Preparation of composite insulated wire: Extruding the resin layer raw material outside the battery core to obtain a composite insulated wire.

Citation Information

Patent Citations

  • Polyetheretherketone-base composite, preparing method thereof and application thereof in friction reduction and wear resistance

    CN104927298A

  • Preparation method of conductive polyether ether ketone composite material

    CN108102292A

  • CF / PEEK composite material with excellent high-temperature mechanical properties and preparation method thereof

    CN111410759A

  • Long fiber reinforced polyether-ether-ketone composite material and preparation method thereof

    CN116376220A

  • High-temperature-resistant thermal response shape memory material as well as preparation method and application thereof

    CN117467129A